Proapoptotic effect of nanoliposomes loaded with hydroalcoholic extract of Hypericum perforatum L. in combination with curcumin on SW48 and SW1116 colorectal cancer cell lines - Farzaneh Rezaeinejad; Hasan Bardania; Farideh Ghalamfarsa; Sajad Hasanzadeh; Farhad Jadidi-Niaragh; Ghasem Ghalamfarsa (Institue of Medicinal Plants, ACECR, 2022)
Background: Colorectal cancer (CRC) continues to be a leading cause of cancer related death in the world and approximately 70 to 75 % of patients with metastatic colorectal cancer survive for up to 1 year after diagnosis. Curcumin (CUR) is a potential chemotherapeutic agent used to treat cancer. There is ample evidence of the inhibitory effects of Hypericum perforatum L. extract (HPE) on cell proliferation and its effects on the induction of apoptosis in various human cancer cell lines. Objective: The purpose of this study was to investigate the proapoptotic effect of HPE and its nanoliposomes (HPE-Lip) and to scrutinize the synergistic and therapeutic potential of HPE/CUR-loaded nanoliposome (HPE/CUR-Lip). Methods: In the present in vitro study, SW1116 and SW48 cell lines were cultured and then treated with different doses of HPE, CUR, bare liposome solely (Lip-Sol), and nanoliposomes loaded with HPE (HPE-Lip), CUR (CUR-Lip) and CUR/HPE (HPE/CUR-Lip) for 24, 48 and 72 hours. Cytotoxicity was measured by MTT assay and apoptosis rate by an annexin-V FITC/propidium iodide double-staining method using flow cytometry. Results: The results showed that cell viability was inhibited in a dose-dependent and time-dependent manner in all groups compared to the control group. The use of nanoliposomes improved the outcomes. HPE/CUR-Lip exhibited higher in vitro cytotoxic and proapoptotic activity against SW1116 and SW48 cell lines (P < 0.05). Conclusion: The findings of this study suggest that the HPE/CUR-Lip complex could provide a potential strategy to achieve a synergistic effect of HPE and CUR in the treatment of colorectal cancer.